PERANAN DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU DALAM REHABILITASI SOSIAL DI KOTA PEKANBARU - Suherman, Lilik; Firdaus, Emilda; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Social services and the funeral the city of Pekanbaru in order to execute the work through the field of rehabilitation, social do the various efforts to top donor problem of social welfare inthe city pekanbaru, however the efforts that have been done that face varoety of obstacle that can be overcome and the effort to do can be run in optimum. This research was given the title role of social services and the funeral the city of pekanbaru. This problem research is whether factors being the cause of the top donor problem of social welfare in the city Pekanbaru, are factors to be obstacles of social services and the funeral the city of Pekanbaru, how did attempt to do social services and the funural the city of Pekanbaru overcome obstacles and social rehabilitation in the city Pekanbaru.This type of research can be classified in this type of juridical sociological research directly on the location or place under study with the source of data primary and secondary, the technique of gathering data from interviews and literature study with analisis and deskriptif kualitatif and method of with drawal conclusions to be made deduktif.The result of the research show factor is poverty,stranded, tuna social, remote, the left, unemployment, human resouces, value individualistik and philosophical value of culture started eroded, culture society konsumtif, obtaclesis an appropriate field of social rehabilitation is limited, human resources less adequate, budget not adequate, the rehabilitation of social a little bit and role as well as the public yet optimum the effort in to overcome obstacles is increased efetifitas kinerja, knowledge and experience of the work, the addition of employees, the field of social rehabilitation, improve the quality of the commencement pembinaan and training effectively, the development of the social bina work, visits to others.Keyword : Role- Social Services and Funeral- Rehabilitation Social